The Impact of the Type of Sport on the Adolescents’ Self-Control - Ranjbar, Sadegh; Shahbazi, Mehdi; Rostami, Reza; Bagherzadeh, Fazlollah (International Journal of Sport Studies for Health, 2024)
Background: Self-control refers to the self-initiated ability to regulate one’s thoughts, emotions, and actions. It plays a crucial role in predicting real-life outcomes. Existing literature highlights self-control as an essential skill that can help individuals achieve their goals and enhance various aspects of their lives.Objectives: The present study aimed to determine the impact of three different sports—middle-distance running, chess, and kata—on the self-control of adolescents.Methods and Materials: The study employed a quasi-experimental method with a pretest-posttest control group design. The statistical population consisted of male adolescents aged 13 to 18 in Kermanshah. 48 participants were selected by a purposive sampling method. Subsequently, the sample members were randomly assigned to three intervention groups (middle-distance running, kata, and chess), along with a control group. Before the intervention, a pre-test was conducted. The experimental groups followed specific protocols for each sport over a two-month period, with training sessions held three times a week, each lasting one hour. Post-tests were administered at the end of the intervention, and a follow-up assessment occurred after two weeks. Tthe Tangney, Baumeister, and Boone Self-Control Scale (2004) and a demographic consent form were the research tools.Findings: The study findings indicated significant differences in self-control scores across pre, post, and follow-up time intervals (Wilks’ lambda = 0.311, F(2,43) = 47.65, p < 0.00123). Additionally, there were significant differences in mean self-control scores among the four groups (middle-distance running, chess, kata, and control) (Wilks’ lambda = 0.199, F(9,102.37) = 10.70, p < 0.00000148). Specifically, middle-distance running demonstrated a significant improvement in self-control among adolescents compared to chess and kata (p ≤ 0.05).Conclusion: Incorporating sports with specific demands, especially middle-distance running, can be an effective intervention for enhancing self-control among adolescents. Engaging in middle-distance running positively impacts self-control, offering young individuals an avenue to develop this essential skill.